1993
DOI: 10.3109/10428199309054731
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Hemolytic Anemia in Chronic Lymphocytic Leukemia Patients Treated with Fludarabine

Abstract: Autoimmune hemolytic anemia (AHA) is a frequent complication of chronic lymphocytic leukemia (CLL). Although the pathogenesis of AHA is still unknown, an imbalance of normal residual T cells is believed to play a central role. Since fludarabine is reported to affect primarily T lymphocytes, we conducted a retrospective study to evaluate the incidence and outcome of AHA in 112 CLL patients treated with fludarabine alone. Eight patients had AHA before therapy; only one achieved remission of both CLL and AHA afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 7 publications
4
44
0
Order By: Relevance
“…Fortunately this was not the case, because the initiation of FAMP led to improvement of AIHA (yet requiring corticoids) as mentioned above. This was probably related to CLL treatment response and this observation is in agreement with DiRaimondo et al 17 In addition, this again underlines the key importance of CLLdirected therapy (ie disease eradication) on the management of AIHA rather than of immune cell engineering.…”
Section: Discussionsupporting
confidence: 77%
“…Fortunately this was not the case, because the initiation of FAMP led to improvement of AIHA (yet requiring corticoids) as mentioned above. This was probably related to CLL treatment response and this observation is in agreement with DiRaimondo et al 17 In addition, this again underlines the key importance of CLLdirected therapy (ie disease eradication) on the management of AIHA rather than of immune cell engineering.…”
Section: Discussionsupporting
confidence: 77%
“…The same immunological mechanisms are suspected during autoimmune reactions and after induction of autologous GVHD. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Finally, the lack of lymphoma relapse in the present series, despite the poor prognostic characteristics of those patients, may suggest that a graft-versus-lymphoma effect could be associated with the occurrence of autoimmune events after transplantation. The contribution of autoimmune events in maintaining disease control after ASCT has been previously suspected.…”
mentioning
confidence: 67%
“…1,8,21 The spontaneous remission of autoimmune manifestations after the period necessary for a full immunological recovery may also suggest that altered immune reconstitution could be important. Finally, other factors suspected to be involved in impaired T cell functions were also found in some patients: previous fludarabine treatment (known to be associated with occurrence of autoimmune hemolytic anemia 22 ) or use of TBI (which may alter thymic function and recovery or function of regulatory lymphocytes 23,24 ). The same immunological mechanisms are suspected during autoimmune reactions and after induction of autologous GVHD.…”
mentioning
confidence: 99%
“…The reported incidence of AIHA after fludarabine treatment varies from 11% to 21%. 21,22 It has been suggested that the profound lymphocytopenia following fludarabine therapy may result in T cell subset imbalance, which in turn may favor the emergence of autoreactive T cells.…”
Section: Figurementioning
confidence: 99%